2020
DOI: 10.1063/5.0013013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fusion plasmas in the cylindrical DTU inertial electrostatic confinement device

Abstract: Inertial electrostatic confinement offers a relatively simple and cost-effective means of generating fusion plasmas for research and industrial applications. Here, we present the experimental setup and discharge characteristics of the inertial electrostatic confinement device at the Dept. of Physics, Technical Univ. of Denmark. Special features of this setup include a cylindrical anode and the novel use of 3D printed soccerball-like cathode grids of different sizes. Measurements with these grids show 25% highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…18,19 Some studies reported that the electrode shape and dimension influence neutron yield. 6,20,21 Other studies focused on the anode material in the context of improving the NPR. 11,22 Elsewhere studies use different cathode materials, operated in a cylindrical anode at < 0.1 Pa gas pressure and < 40 kV applied voltage, in the context of cathode surface fusion and its significant contribution to the NPR.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Some studies reported that the electrode shape and dimension influence neutron yield. 6,20,21 Other studies focused on the anode material in the context of improving the NPR. 11,22 Elsewhere studies use different cathode materials, operated in a cylindrical anode at < 0.1 Pa gas pressure and < 40 kV applied voltage, in the context of cathode surface fusion and its significant contribution to the NPR.…”
Section: Introductionmentioning
confidence: 99%
“…At the Technical University of Denmark (DTU), we have recently acquired and developed two experimental plasma devices for research and education in fusion-relevant laboratory plasmas: a small tokamak, NORTH [10], for magnetic confinement of plasmas, and an inertial electrostatic confinement device, the DTU Fusor [11], for studies of fusion plasmas. A third experiment, a linear plasma device, is currently being commissioned.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the beambeam or beam-background collision initiates the fusion process as a result of which neutrons are produced 7,9,10 . Since the development of the very first IECF device 11,12 , the researchers carried out geometrical and technical modification of the device in order to increase the neutron yield [13][14][15][16][17][18] , over the years. Recently, our team of researchers at CPP-IPR have a) Also at:Homi Bhabha National Institute, Anushaktinagar, Mumbai, Maharashtra, 400094, India; Email:smruti@cppipr.res.in carried out experiments in the cylindrical IECF device with some success in neutron production and its application in explosive detection [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed x-ray has been produced in a table-top cylindrical IECF device by another group 26 . In some experiments, both neutron and x-ray has been produced during negative polarity of the grid in which the neutrons are produced from the central region and the x-ray from the wall region of the chamber 16,23 . However, due to the broad x-ray emitting zone the x-ray flux is less in such cases and hence, it has limitations as far as x-ray applications are concerned.…”
Section: Introductionmentioning
confidence: 99%